Proposição de um método para avaliação da qualidade de faixas de pedestres - Sassaron, Mariana Luiza da Silva (Universidade Federal de São Carlos, 2023)
Traffic signs are important tools in ensuring road safety and the operation of transportation systems. They help users to understand traffic and adopt appropriate behaviours to ensure safety and fluidity of traffic . Considering the relevance of signals and the need for them to be efficient and have quality for their full operation, the following work elaborates a method for evaluating the quality of pedestrian crosswalks. With the use of the Analytic Hierarchy Process (AHP) developed by Saaty (1977) and an onymous questionnaires of public research , a general equation was obtained which can be used in the evaluation of different crosswalks . Furthermore, the work presents the results of its application in a case study at the Federal University of São Carlos, S ão Carlos campus, with an average score of the 42 crosswalks analysed equal to 3.86, on a scale of 0.00 to 5.00. It should be noted, however, that the worst lanes were further away from areas with the highest demand, while more critical points, with a higher volume of pedestrians, had better quality crosswalks.
Proposition of a method to evaluate the quality of pedestrian crosswalks
Keywords: Segurança viária; Índices de qualidade; Sinalização; Faixas de pedestres; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES